Comic heroes or saviours? Constructing alternative identities in a social critical approach to the teaching of English as a foreign language. - Emmanouilidou, Maria Dimitrios; Emmanouilidou, Sophia Dimitrios; Papademetriou, Efi (Preschool and Primary Education, 2016)
Current educational systems primarily focus on the verbal and logico-mathematical aptitude of students, thus neglecting the cultivation of visual literacy and critical literacy skills, although the ubiquity of images in school textbooks necessitates the inclusion of a ‘visual grammar’ metalanguage in educational practices. The aim of the present paper is to present and analyse how a group of eighteen sixth grade students of an EFL classroom in a state primary school in Thessaloniki managed to ‘deconstruct’ the depiction of superheroes/heroines in comic books or action movies, in an effort to represent them in a more humane and mundane way, where their super powers are summoned to the advantage of a society in need. The overall organization of the instructional intervention is built on an introductory phase, a main phase and a follow-up phase. The analysis of the students’ compositions relies on the application of the principles of critical visual literacy and the results display that through the process of scaffolding, the students can reject dominant representations of power and reconstruct cliché identities by re-exploring pre-existing roles. The end result, that is the classroom calendar compiled by twelve multimodal texts, manifests the students’ skilful utilization of both visual and verbal semiotic resources in a balanced way, with a view to transmitting their social messages taking into account the broader social, cultural and political context within which power relations and social roles constantly evolve and are constructed.